Over-expression of Toll-like receptor 2 up-regulates heme oxygenase-1 expression and decreases oxidative injury in dairy goats. Issue 1 (December 2017) - Deng, Shoulong; Yu, Kun; Jiang, Wuqi; Li, Yan; Wang, Shuotian; Deng, Zhuo; Yao, Yuchang; Zhang, Baolu; Liu, Guoshi; Liu, Yixun; Lian, Zhengxing
Abstract Background Mastitis, an infection caused by Gram-positive bacteria, produces udder inflammation and oxidative injury in milk-producing mammals. Toll-like receptor 2 (TLR2) is important for host recognition of invading Gram-positive microbes. Over-expression ofTLR2 in transgenic dairy goats is a useful model for studying various aspects of infection with Gram-positive bacteria, in vivo. Methods We over-expressedTLR2 in transgenic dairy goats. Pam3CSK4, a component of Gram-positive bacteria, triggered the TLR2 signal pathway by stimulating the monocytes-macrophages from theTLR2 -positive transgenic goats, and induced over-expression of activator protein-1 (AP-1), phosphatidylinositol 3-kinase (PI3K) and transcription factor nuclear factor kappa B (NF-κB) and inflammation factors downstream of the signal pathway. Results Compared with wild-type controls, measurements of various oxidative stress-related molecules showed thatTLR2, when over-expressed in transgenic goat monocytes-macrophages, resulted in weak lipid damage, high level expression of anti-oxidative stress proteins, and significantly increased mRNA levels of transcription factor NF-E2-related factor-2 (Nrf2) and the downstream gene, heme oxygenase-1 (HO-1). When Pam3CSK4 was used to stimulate ear tissue in vivo the HO-1 protein of the transgenic goats had a relatively high expression level. Conclusions The results indicate that the oxidative injury in goats over-expressingTLR2 was reduced following Pam3CSK4 stimulation. The underlying mechanism for this reduction was increased expression of the anti-oxidation geneHO-1 by activation of the Nrf2 signal pathway.